Effects of increasing phytase in nursery pig diets and determining the impact of increasing lysine in lactating sows - Gourley, Kiah Marie (Kansas State University, 2017)
Two experiments using a total of 646 nursery pigs were used to determine the effects of increasing phytase on nursery pig growth performance and bone ash characteristics. Two experiments using a total of 821 sows were used to determine the impact of increasing standardized ileal digestible (SID) lysine (Lys) in lactating sows. Experiment 1 determined the available phosphorus (aP) release of Natuphos E 5,000 G phytase in nursery pigs. Increasing phytase from 0 to 1,000 FTU/kg in phosphorus deficient diets improved nursery pig performance and bone ash characteristics. Using percentage bone ash and formulated phytase concentrations, an equation was developed to predict aP release up to 1,000 FTU/kg of Natuphos E phytase. Experiment 2 was conducted to determine the effect of Superdosing Natuphos E 5,000 G phytase on nursery pig performance and bone ash characteristics. Increasing phytase in diets marginal in P improved pig performance and bone ash values. Increasing phytase in P sufficient diets improved bone ash percent and tended to improve feed efficiency. Experiments 3 and 4 determined the impacts of increasing SID Lys in primiparous and multiparous lactating sows and their litters. In Exp. 3, increasing SID Lys above 0.80% in primiparous sows decreased backfat loss, but had no effect on sow BW loss, ADFI or litter gain. Conception rate at d 30 and percentage born alive tended to improve at 0.95% SID Lys. In Exp. 4 with mixed parity sows, increasing SID Lys to 1.05% increased sow weaning BW, litter gain, and reduced weight loss in lactation. Sow backfat loss increased as SID Lys increased from 0.75 to 1.20%, however loin eye depth loss was reduced as SID Lys increased. Percentage of females bred by d 7 after weaning was improved in primiparous females with increasing SID Lys, however no difference was observed in multiparous sows.
Keywords: Lactating sows; Lysine; Phosphorus; Phytase; Nursery pigsBone ash